Penggunaan Maggot (Hermetiaillucens) Dalam Pakan Ayam Ras Petelur: The Use of BlackSoldierFlyer (Hermetia illucens) Larvaein Feed of Laying Hens - Sumiati Sumiati; D. K. Purnamasari; Erwan Erwan; Syamsuhaidi Syamsuhaidi; K.G. Wiryawan; Ahmad Nur Alfin Rizki; Mujaddid Isnaini (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
The research aimed to determine the use of Hermetia Illucens maggot in feed on the production of laying hens. 80 laying hens aged 6 months were grouped into 4 treatment groups,5 replicates, each replication consisted of 4 tails. The feed provided consisted of 50% corn+20.47% rice bran+29.52% layer concentrate (P0), 45% corn+27% rice bran+23% layer concentrate+5% maggot (PI), 45% yellow corn +27.73% rice bran+17.27% layer concentrate+10% maggot (PII), 40% corn+34.33% rice bran+10.67% layer concentrate+15% maggot ( PIII).. The data obtained were analyzed by a completely randomized design. The results of the study average daily egg production for each treatment were 61.97% (P0), 73.57% (PI), 64.10% (PII) and 59.65% (PIII). The average egg weight was 55.35g/egg/head (P0), 556.47g/egg/head (PI), 55.75 g/egg/head (PII) and 55.84g/egg/head (PIII). Feed consumption was 110.23 g/head/day (P0), 112.21g/head/day (PI), 111.75g/head/day (PII) and 103.55g/head/day. Feed conversion was 3.45 (P0)., 2.81 (PI), 3.20 (PII) and 3.21 (PIII). Egg protein was 12.17% (P0), 12.98% (P1), 13.83% (PII), 14.53% (PIII). Egg cholesterol was 149.25mg/dl (P0), 153.75mg/dl (P1), 181.25mg/dl (P2) and 175.00mg/dl (P3). Beconcluded that the use of Hermetia Illucens maggot 5%, 10%, 15% in feed has not significant effect (P>0.05). on the egg production, egg weight, consumption and feed conversion and significant effect (P< 0.05) on the protein and colesterol of laying hens.